In vitro susceptibilities of normal human skin fibroblasts to oncoviruses, and the decreased susceptibility to HSV of fibroblasts from untreated Hodgkin's patients. - Ebbesen, P. (Nature Publishing Group, 1981)
Fibroblast cultures established from the skin of 56 healthy controls and 15 untreated Stages I and II Hodgkin's patients (HD) were studied in their 3rd, 4th and 5th in vitro passage with respect to transformation with Simian sarcoma virus (SSV) and SV40 and with respect to replication of herpes simplex virus (HSV) Types 1 and 2, pox virus and interferon release. Susceptibility to the 5 viruses varied independently, except for an inverse correlation between susceptibility to SSV and HSV. HD cultures showed a depressed replication of both types of HSV. There was a borderline (P = 0.02) correlation between magnitude of HSV replication and presence of HL-A type B-w44, but this does not explain the HD control difference. Furthermore, the level of serum antibodies to HSV common antigen was not related to magnitude of in vitro replication. The results thus speak against generally enhanced cellular susceptibility to HSV as a reason for the high titres of serum antibodies to HSV in HD patients.